Depiction of the Philosophical Meaning of Malang Masks based on Augmented Reality as a Learning Medium for Nusantara Art - Sidyawati, Lisa; Soesanto, Soesanto; Lestari, Wahyu (Jurnal Pendidikan Multimedia (Edsence), 2024)
Masks have various roles and functions in various regions and countries, including the use of masks as manifestations, worship tools, funeral equipment, dance costume attributes, and others. Masks are considered as carvings that reflect individual characteristics. In Malang, East Java, Indonesia, there is a Malang Mask tradition that is an icon of the city and inspired by the Panji story. Some masks are kept in museums, while others are used as props for the Malang Mask Dance. The Panji Museum and Kampung Topeng are places that preserve the history of the Malang Mask so that it does not become extinct. Unfortunately, these places do not provide complete information about the character of each mask, so visitors are often confused. Therefore, researchers developed an application that can present infographics of the character of each mask along with its philosophical meaning. The development method used is the Borg Gall model, which is simplified into 7 steps due to time constraints. The result is an Augmented Reality-based Panji Story Mask infographic application that depicts the masks and costumes worn by the dancers along with their philosophical meanings. The depiction of the character of each mask is expected to be an example for the younger generation to understand good and bad traits. This digital application is also expected to improve the image of the museum and become a learning medium for students and the general public.